Melanonychia Secondary to Long-Term Treatment with Hydroxycarbamide: An Essential Thrombocytosis Case - Umit Yavuz Malkan; Gursel Gunes; Eylem Eliacik; Okan Yayar; Ibrahim Celalettin Haznedaroglu (Case Reports in Hematology)
Hydroxycarbamide is used in the treatment of essential thrombocytosis and other myeloproliferative disorders. We report the case of a 63-year-old woman with essential thrombocytosis who had melanonychia after the long-term use of the hydroxycarbamide with a dose of 1000 mg/day. Two years after the initiation of the hydroxycarbamide, our patient had pain on her toes and melanonychia on her nails. Hydroxycarbamide treatment was discontinued because of pain and she was given anagrelide treatment. The pathogenesis of melanonychia secondary to long-term hydroxycarbamide treatment is not yet well understood. Some investigators suggested that genetic factors, induction of melanocytes, and some changes in nail matrix could be the reason of hydroxycarbamide related melanonychia. Our patient has suffered color changes in her nails as well as pain that made us doubtful for a beginning of ulceration besides melanonychia. Maybe early clinical reaction of discontinuation of the drug has prevented more severe side effect like ulceration in our patient. Also side effect of hydroxycarbamide has developed more slowly in our patient compared to other patients in the mentioned study. To conclude, long-term hydroxycarbamide treatment can cause mucocutaneous side effects and more studies should be done in future in order to reveal the underlying mechanism.